Role of plasma exchange in stiff person syndrome. (June 2019) - Albahra, Said; Yates, Sean G.; Joseph, David; De Simone, Nicole; Burner, James D.; Sarode, Ravi
Abstract: Objective: Stiff person syndrome (SPS) is commonly associated with antibodies directed against 65-kDa glutamic acid decarboxylase (GAD65). Therapeutic Plasma Exchange (TPE) has been used as an adjunct therapy in patients who do not respond well to conventional treatment, which includes immunosuppression therapies, anti-anxiety medications, muscle relaxants, anticonvulsants, and pain relievers. Methods: We retrospectively analyzed the clinical data and outcomes of ten patients with the clinical diagnosis of anti-GAD65 positive SPS in which TPE was employed to improve symptoms refractory to conventional treatment during an eight-year period. Results: TPE was initiated as complementary therapy in patients with worsening of symptoms characteristic of SPS. Six patients underwent chronic treatment with TPE following an initial course, of which the frequency of TPE was guided by the clinical response. Two patients only had transient improvements with further disease progression. Four patients developed a relapse of symptoms when the interval between procedures was increased. One of the four patients dependent on TPE had worsening of symptoms following complete cessation of TPE due to lack of insurance coverage. Four patients underwent only an acute hospitalized course of treatment with TPE; one demonstrated complete resolution of symptoms; one had a partial response; and two experienced no improvement. Conclusion: Our study supports previous reports that TPE may be beneficial for the management of patients with anti-GAD65 positive SPS, both for acute exacerbations and long-term maintenance, either as an adjunct therapy, or in lieu of treatment with disease modifying agents.